Enhancing Customer Referral Values: How Control Based Contributions Among Mobile Legends Players in Jakarta - Napitupulu, Wempi Darwis; Yolanda Soedibyo (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This study investigates the impact of various contributions - Control Based Contributions, Collaborative Contributions, Individual Contributions, and Calculated Contributions - alongside Customer Learning/Knowledge Values, Customer Influences Values, and Customer Referral Values on Customer Loyalty among Mobile Legends players in Jakarta. With the rising popularity of online mobile games, particularly Mobile Legends, understanding these dynamics is crucial for game developers aiming to foster loyalty and enhance user engagement. This research addresses significant gaps in the literature regarding the effects of gamification and customer involvement in online gaming, providing insights that could inform marketing strategies and loyalty programs within the gaming industry.